Milling parameters optimization for surface quality - Dias, Tânia Maria Costa (2017)
The Taguchi method is a powerful tool to experiment design optimization and is used in this work to optimize the cutting parameters, which reduce the chatter ef-fect on surface quality. The present study includes feed per tooth, cutting speed, radial and axial depth of cut as control factors. An orthogonal array of L16 was used with the ANOVA analyses in order to identify the significant factors asso-ciated to the surface roughness and chatter vibration in three different directions. The optimal cutting combination for the surface finishing was determined through the analysis of surface roughness. This are correlated with the vibrations levels recorded during the experimental tests. The study was carry-out by machining a hardened steel block with tungsten carbide coated tools. The results led to the minimum of arithmetic mean surface roughness of 1.05 µm which corresponded to a minimum of the mean vibration level.